RR soybean seed quality after application of glyphosate in different stages of crop development - Albrecht,Leandro Paiola (2012)
In consequence of several studies and speculations concerning the issue of RR transgenic soybean after the application of glyphosate, additional scientific investigations became necessary to clarify the actual viability of the product use when applied in different developmental stages of the soybean crop. Therefore, this study was aimed to evaluate the physiological quality as well as seed health quality of RR soybean subjected to application of the herbicide glyphosate in different phonological stages of the transgenic soybean, cultivar CD 219RR. For this, an experiment with a complete block experimental design with treatments randomly distributed within the block, with four replications, was carried out. The assessed treatments were foliar sprayings of glyphosate in three increasing dosages [0 (control); 1,440 g ha-1; and 2,880 g ha-1] of acid equivalent, applied in two crop developmental stages: vegetative (V6) and reproductive (R2). The variables assessed were: germination; first count of germination; fresh and dry mass of seedlings, lengths of seedling and root; vigor and viability by the tetrazolium test; and seed health quality. Glyphosate application may adversely affect physiological quality of RR soybean seeds, when applied in dosages varying from 1,440 to 2,880 g acid equivalent per hectare at the stages V6 and R2.